PAYER PERSPECTIVES ON FUTURE ACCEPTABILITY OF COMPARATIVE EFFECTIVENESS AND RELATIVE EFFECTIVENESS RESEARCH. (14th July 2015) - Moloney, Rachael; Mohr, Penny; Hawe, Emma; Shah, Koonal; Garau, Martina; Towse, Adrian
Abstract : Objectives : Our objective was to gather perspectives from payers on how comparative effectiveness research (CER) in the United States and relative effectiveness (RE) research in Europe will impact evidentiary standards for access decisions of new drugs by 2020. Methods : We conducted semi-structured interviews with fourteen senior officials representing public and private payers, health technology assessment groups, and pricing and reimbursement bodies in the United States and Europe. An online survey assessed current use of CER/RE evidence and potential trends that might influence its use for decision making by 2020. A semi-structured interview elicited payers' definitions of CER/RE and was structured around four hypothetical cases resembling drugs expected to be more common or poised to create policy challenges by 2020. Topics included acceptance of study designs and analytic methods associated with CER/RE. A systematic content review was done to extract relevant information. Results : According to key informants, randomization will remain an essential component for assessing comparative or relative effectiveness. They anticipate greater use of policy levers such as conditional reimbursement or prior authorization to manage diffusion of new drugs. Case studies provided important insights into situations when certain types of CER evidence may be acceptable (e.g., observational data when differences between drugs are largely convenience). Conclusions : Industry perceptions that CER/RE will change payers' evidentiary requirements in the future are consistent with our findings. Growing investment in payers' own data and increased reliance on policy tools to control diffusion of new drugs may also influence the type of evidence industry will be required to produce by 2020.